Prognostic Significance of Clinical and Post-Neoadjuvant Chemotherapy Associated Histomorphological Parameters in Osteosarcoma: A Retrospective Study from a Tertiary Care Center - Vangala, Navatha; Uppin, Shantveer G.; Rao, K. Nageshwara; Chandrasekhar, P.; Gundeti, Sadashivudu (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Osteosarcoma is the most prevalent bone cancer in adolescents. Neoadjuvant chemotherapy (NACT) followed by resection is the current modality of treatment for osteosarcoma. Histological evaluation of extent of tumor necrosis on resection is a well-established prognostic indicator in osteosarcoma correlating with survival in most cases.Objectives The main objective of this study was to establish prognostic significance of various clinical and histological parameters post-NACT in osteosarcoma and to compare the integrated prognostic index proposed by Chui et al, with grading of response to NACT by Huvos and Rosen for osteosarcoma.Materials and Methods This is a retrospective study done over a period of four years and includes 47 cases of osteosarcoma treated with NACT. All slides were reviewed and association of various clinical and histological parameters with overall survival was assessed with chi-squared test and Cox-regression analysis.Results Statistical analysis revealed the prognostic significance of age at presentation, anatomic site, primary tumor size, metastatic status, and clinical stage. Histological parameters such as mitosis ≥10/10hpfs, ≥10% residual tumor were significantly associated with poor survival. Tumor necrosis ≥ 90% (excluding areas of hemorrhage, fibrosis and acellular osteoid) was significantly associated with increased survival. An integrated prognostic index formed by combining above parameters gives a better estimate of overall survival compared with residual disease or necrosis alone.Conclusion Integrated prognostic index improves prognostication in patients treated for osteosarcoma.
Keywords: osteosarcoma; Huvos and Rosen grade; integrated prognostic index